A digital torsimeter for torsion testing of materials and shear elasto-plastic parameters evaluation Torcímetro digital para teste de torção em materiais e avaliação dos parâmetros elasto-plásticos de cisalhamento - Betemps M.I. (2021)
© 2021, Universidade Federal do Rio de Janeiro. All rights reserved.In this work, the project, the main components and the results obtained with the prototype of a digital tor-siometer that was built to measure the variation of the torsion angle in mechanical tests of materials are shown. A magnetic encoder model AS5048A was used in this device. This encoder has 14 bits of resolution and an Arduino Mega 2560 microcontroller board was used for data processing. In addition to the low cost of electronic and mechanical components, another advantage of the measurement system developed is the large amount of free applications available for processing and acquiring data with the microcontroller board used. Tests were carried out to verify the accuracy in the angular variation readings and torsion tests with aluminum tubular specimens (AA6351T6 alloy) to evaluate the performance of the measurement system in monotonic tests. The Ramberg-Osgood relationship was used to describe the behavior of the material and the shear stresses were evaluated using nonlinear relationships proposed by different authors. The results obtained in-dicate that the digital torsiometer presented satisfactory results for obtaining the torsion angle and the main advantages of this device include the measurement of the non-contact torsion angle, linearity, good accuracy over the entire measurement range, unlimited measurement range, reduced size and low cost for confection.